Kurikulum Berbasis Kompetensi (Konsep dan Implementasi) - anarisa, anarisa (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Efforts to improve the quality of education by conducting curriculum development are a necessity, because there are a number of pillars as well as the direction of the implementation of education in schools. In accordance with global demands ahead of the enactment of AFTA (Asean Free Trade Area) and AFLA (Asean Free Labor Area) the demands of the education world are increasingly complex. The world of education is required to be able to produce skilled workers who are able to exist and survive in this global development. because to meet the demands of these developments, improvement and renewal of various components of education especially the educational curriculum becomes an urgent thing to do, because in reality the 1994 curriculum was no longer relevant to deliver students to be able to compete with the global development of society for the government through the Ministry of National Education in academic year 2004/2005 will provide a new curriculum called the Competency-Based Curriculum (CBC) with a variety of studies and planning that is expected to be able to produce quality HR and be able to answer the global challenges of society.